Characterization of stiffness degradation caused by fatigue damage of additive manufactured parts. (5th November 2016) - Ziemian, C.W.; Ziemian, R.D.; Haile, K.V.
Abstract: A study of the cyclical fatigue behavior of additive manufactured components, fabricated by the fused deposition modeling (FDM) process, is presented. Experimentation was designed to focus on the effect of deposition strategy or specimen mesostructure on tensile fatigue life and effective stiffness. Testing included consideration of unidirectional laminates with parallel plies having fiber orientations ranging from θ = 0° to θ = 90°, and bidirectional laminates with alternating orthogonal plies that form a layering pattern of θ°/(θ - 90°) fiber orientations. Results highlight the orthotropic behavior of FDM components and suggest that tensile performance is improved by aligning fibers of unidirectional laminae more closely with the axis of applied stress. The bidirectional laminae display incrementally improved tensile fatigue performance from what appears to be an offsetting effect associated with alternating orthogonal layers. An empirical model of effective elastic modulus and an analytical model of the accumulated damage state, as defined on the basis of stiffness degradation during cyclical loading, are presented as functions of specimen mesostructure. The actual damage accumulation due to cyclical loading is compared with the model predictions, and the coefficient of determination R 2 indicates reasonable agreement for each factor combination. Graphical abstract: Highlights: Relationship between deposition strategy and FDM component stiffness is verified using composite laminate theory FDM component stiffness degrades during cyclical fatigue loading due to multiple damage modes Stiffness-based damage of FDM specimens demonstrates nonlinear, 3-stage progression similar to that of composite materials Damage accumulation rate is greatest in first 3% of fatigue life due to crazing, fiber cracking, delamination, & void changes Damage rate in the final 2-3% of fatigue life is often high due to fiber fracture